Drosophila importin-7 functions upstream of the Elmo signaling module to mediate the formation and stability of muscle attachments - Liu, Ze Cindy (The Company of Biologists, 2013)
Establishment and maintenance of stable muscle attachments is essential for coordinated body movement. Studies in Drosophila have pioneered a molecular understanding of the morphological events in the conserved process of muscle attachment formation, including myofiber migration, muscle–tendon signaling, and stable junctional adhesion between muscle cells and their corresponding target insertion sites. In both Drosophila and vertebrate models, integrin complexes play a key role in the biogenesis and stability of muscle attachments through the interactions of integrins with extracellular matrix (ECM) ligands. We show that Drosophila importin-7 (Dim7) is an upstream regulator of the conserved Elmo–Mbc→Rac signaling pathway in the formation of embryonic muscle attachment sites (MASs). Dim7 is encoded by the moleskin (msk) locus and was identified as an Elmo-interacting protein. Both Dim7 and Elmo localize to the ends of myofibers coincident with the timing of muscle–tendon attachment in late myogenesis. Phenotypic analysis of elmo mutants reveal muscle attachment defects similar to those previously described for integrin mutants. Furthermore, Elmo and Dim7 interact both biochemically and genetically in the developing musculature. The muscle detachment phenotype resulting from mutations in the msk locus can be rescued by components in the Elmo signaling pathway, including the Elmo–Mbc complex, an activated Elmo variant, or a constitutively active form of Rac. In larval muscles, the localization of Dim7 and activated Elmo to the sites of muscle attachment is attenuated upon RNAi knockdown of integrin heterodimer complex components. Our results show that integrins function as upstream signals to mediate Dim7–Elmo enrichment to the MASs.